Tourism Management in Kinabalu Park. An Analysis of nature of goods in meeting sustainable tourism - Goh, Hong Ching; Mohd Yusoff, Mariney (2010)
In nature-based tourism destination, sustainable tourism is a more responsible form of tourism seeks to minimize the undesirable impacts of tourism development in ecological sensitive areas apart from contributing to nature conservation. While these objectives must be achieved, it is also important to ensure a high level of tourist satisfaction which is central to the survival of tourism business. In protected areas, park management is traditionally a responsibility of public sector. While public sector is said to be in a better position in securing the interest of public, tourism business is not their forte but private sector due to the heavy bureaucratic nature of the former and the profit-driven nature of the latter. Kinabalu Park is a famous nature-based tourism destination in Malaysia for its flora diversity and splendid mountainous landscape. By borrowing the case of Kinabalu Park, this paper aims to reveal some arising issues in park management resulted from the involvement of private sector in protected areas based on the discourse on nature of goods and services.